Cognitive evaluation of computer-drawn sketches - Visvalingam, Maheswari; Dowson, Kurt
First paragraph: Global terrain data is becoming increasingly available in various forms, such as contours, Triangulated Irregular Networks (TINs) and grid Digital Elevation Models (DEMs) . DEMs are also known as height fields and as altitude matrices. The research reported in this paper contributes to three strands of research being undertaken within the Cartographic Information Systems Research Group (CISRG) of the University of Hull. It contributes to research on a) the automatic derivation of minimalist sketches of grid DEM data, b) methodology for the evaluation of underpinning line generalisation algorithms, and c) the abstraction of subsets of points for representing the terrain as a Triangulated Irregular Network (TIN). This paper focuses on the first two aims. Field sketching of landscapes and the drawing of generalised block diagrams were valued as a scientific art and formed a part of the cartographer's training in the pre-computer era (lobeck, 1924, Raisz, 1938) . With the availability of systems for visualising terrain in various ways, the artistic methods of relief representation have largely been ignored within Geographical Information Systems (GIS) . Th is is partly because our understanding of the cognitive processes involved in sketching is still insufficient. Yet engineering firms, such as the co-sponsors of this research project, and several other applications require artists for sketching the landscape.
Keywords: Cartography – Data processing; Computer science